If f(x)= x^3 + 2x^2 - 3x, and g(x) is a translation of f(x) 2 unites to the right, what is the equation for g(x)?

1 Answer | Add Yours

hala718's profile pic

hala718 | High School Teacher | (Level 1) Educator Emeritus

Posted on

Given that :

`f(x)= x^3 + 2x^2 -3x`

Given that g(x) is a transformation of f(x) 2 units to the right.

We know that if we move the function 2 units to the right, then x becomes (x-2)

`==gt g(x)= f(x-2) `

`==gt g(x)= (x-2)^3 + 2(x-2)^2 -3(x-2)`

Now we will expand and simplify.

`==gt g(x)= (x^3 -6x^2+12x -8) + 2(x^2-4x+4) -3x+6 `

`==gt g(x)= x^3 -4x^2 +x + 6`


We’ve answered 317,288 questions. We can answer yours, too.

Ask a question